"I Consider Myself a Mathematics Teacher": the understanding that elementary school teachers have about themselves as mathematics educators "Eu me Considero Professora de Matemática": a compreensão que as professoras dos ciclos iniciais têm de si mesmas como educadoras matemáticas - Roberto Antonio Marques (Universidade Estadual Paulista, 2008)
In this article I analyzed aspects of the understanding that teachers of the beginning grades of elementary school have regarding themselves as Mathematical Educators. Using Discourse Analysis resources, I sought to identify and discuss the manners in which the interviewees structure their speech, assume and respond (to and for) enunciations and positions in the school context. The analysis of the interviews shows that the teachers' understanding of themselves as Mathematical Educators goes through the mediations that are established while they seek solutions for challenges to their condition and practice as teachers. The concerns identified in their speech indicate the need for addressing cultural aspects of the conditions for teaching mathematics in training courses for these teachers. Neste artigo analisei aspectos da compreensão que professoras dos ciclos iniciais do Ensino Fundamental têm de si mesmas como Educadoras Matemáticas. Lançando mão de recursos da Análise do Discurso, busquei identificar e discutir os modos pelos quais as entrevistadas estruturam suas falas, assumem e respondem a/por discursos e posições no cenário escolar. A análise das entrevistas revela que a compreensão que as professoras têm de si mesmas como Educadoras Matemáticas passa pelas mediações que elas estabelecem na busca de soluções para os desafios de sua condição e prática docente. As preocupações identificadas nos seus depoimentos apontam para a necessidade dos cursos de formação de professores contemplarem os aspectos culturais que permeiam a condição docente de quem ensina Matemática. Palavras-chave: Condição e Prática Docente. Formação de Professores. Educação Matemática.